Islamic Education And Modernity In The Middle East: Egypt Case Study - Eman Taha Mohamed (GoAcademica Research & Publishing, 2019)
This article discusses Islamic education and modernity in the Middle East. Modern culture began to be known in Egypt since the emergence of Napoleon Bonaparte in the early 19th century in this country. However, at the time of Muhammad Ali, the transition from traditional education to modern education began. Furthermore, during the Ismail Pasya era, due to the reorganization of culture, traditional education began to compete with advanced secular education.